2023
DOI: 10.3390/polym15040798
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Design Method of an Evolutionary Mold Cooling Channel Using Biomimetic Engineering

Abstract: In this study, an evolutionary cooling channel, a new methodology for designing a conformal cooling channel, was proposed. This methodology was devised by imitating the way that a plant’s roots grow towards a nutrient-rich location. Additionally, Murray’s law was applied to increase the cooling efficiency through minimizing the pressure loss of the cooling water inside the cooling channel. The proposed method was applied to the specimen shape to verify the concept, and it was confirmed that efficient cooling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The cooling goal of the cooling channel is to make the plastic parts cooled evenly, based on this idea, many researchers get inspiration from nature and daily life, apply it to the design of conformal cooling channel through complex algorithms, and get good results [24][25][26][27][28][29] . According to the growth mechanism of plant roots, the product is divided into smaller domains by CVD algorithm and the cooling channels are made by connecting the thermal centers with the binary branching law [24] .…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling goal of the cooling channel is to make the plastic parts cooled evenly, based on this idea, many researchers get inspiration from nature and daily life, apply it to the design of conformal cooling channel through complex algorithms, and get good results [24][25][26][27][28][29] . According to the growth mechanism of plant roots, the product is divided into smaller domains by CVD algorithm and the cooling channels are made by connecting the thermal centers with the binary branching law [24] .…”
Section: Related Workmentioning
confidence: 99%
“…According to the growth mechanism of plant roots, the product is divided into smaller domains by CVD algorithm and the cooling channels are made by connecting the thermal centers with the binary branching law [24] . Furthermore, in [25], the authors proposed a design methodology for a conformal cooling channel minimizing the stagnation of cooling water by mimicking the growth of plant roots. The binary branching rule was used for the cooling channel so that two child cooling channels were differentiated from one parent cooling channel.…”
Section: Related Workmentioning
confidence: 99%
“…It was found that CCC shows an average temperature peak at 58.78 °C. Choi et al [ 10 ] used the biomimetic engineering method to design the CCC. The results showed that the pressure loss was reduced by about 10 times.…”
Section: Introductionmentioning
confidence: 99%
“…Minh et al [9] optimized the cooling channel in injection molds using Taguchi-integrated principal component analysis. It was found that CCC shows an average temperature peak at 58.78 • C. Choi et al [10] used the biomimetic engineering method to design the CCC. The results showed that the pressure loss was reduced by about 10 times.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated a 9.26% reduction in warpage for the cup-shaped injection-molded part when CC was used, as opposed to the conventional cooling channel. Minh et al [9] optimized injection mold cooling channels using Taguchi-integrated principal component analysis, revealing that CC resulted in an average temperature peaking at 58.78 • C. In the biomimetic engineering approach by Choi et al [10], CC design led to a remarkable ten-fold reduction in pressure loss and approximately 46% improvement in temperature deviation compared to conventional cooling channels. Torres-Alba et al [11] proposed an innovative CC system with high resistance to warping, demonstrating a 66% reduction in cycle time and an 81.88% decrease in residual stress.…”
Section: Introductionmentioning
confidence: 99%